Penyesuaian Diri Pada Mahasiswa Tahun Pertama Di Fakultas Psikologi Universitas Muhammadiyah Surakarta - Nurfitriana, Pipit; Dr. Nanik Prihartanti, M.Si, Dr. Nanik Prihartanti, M.Si (2017)
First-year students when entering college certainly make adjustments to their environment, from the transition to the Junior High School Higher Education. During the adjustment process, first-year students undergo various changes that occur in the university environment both academically and socially, with the changes that happen to appear the problems experienced by first-year students. This study aims to understand and describe Adjustment on Freshman Forces 2015/2016 at the Faculty of Psychology, University Muhammaiyah Surakarta, conducted on 15 students of the Faculty of Psychology UMS. The method used in this research is descriptive qualitative method. From the research that has been done shows that the First-year students of the Faculty of Psychology UMS had various problems during the process of adjustment in universities both in terms of academic and non-academic, students who do not kos (Domicile Surakarta) has adjustment better than the students kos (Outer Islands and Outer City), first year student of Faculty of Psychology UMS has its own way to adapt, first-year student academic achievement of all above 3.00. With details, 6 informants (40%) have a IPK > 3:50 and the remaining 9 informants (60%) have a IPK of 3:00 - 3.49.